Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Pegawai Sekretariat DPRD Provinsi Kalimantan Timur - Riska Damayanti; Fenty Fauziah; Mursidah Nurfadillah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
Employee performance is a crucial factor in determining the effectiveness of public organizational functions. This study aims to analyze the influence of transformational leadership style and organizational culture on employee performance within the Secretariat of the Regional House of Representatives (DPRD) of East Kalimantan Province. This research employs a quantitative approach using a survey method, with respondents selected through simple random sampling from the total employee population. The sample consisted of 144 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 29, in order to examine the partial and simultaneous effects of the independent variables on the dependent variable. The results indicate that both transformational leadership style and organizational culture have a positive and significant impact on employee performance, both individually and simultaneously. These findings highlight the importance of leaders who are capable of inspiring their teams, as well as the implementation of a strong organizational culture in fostering a professional and productive work environment that aligns with the institution’s goals.